Influence of photopolymerization light source on enamel shear bond strength after bleaching - Loretto,Sandro Cordeiro (2004)
This study evaluated the influence of 3 different photopolymerization sources on enamel shear bond strength after bleaching with 10% carbamide peroxide. Seventy-two incisive bovine teeth were randomly divided into 6 groups (n=12) according to bleaching treatment and photopolymerization source used: G1 - Bleached / Halogen lamp; G2 - Not bleached / Halogen lamp (control); G3 - Bleached / Light-emitting diodes (LED); G4 - Not bleached / Light-emitting diodes (LED) (control); G5 - Bleached / Xenon plasma arc; G6 - Not bleached / Xenon plasma arc (control). Experimental groups were exposed to bleaching agent for a period of 14 days, with a daily contact of 4 h and then stored in artificial saliva at 37ºC. Control groups were stored in artificial saliva at 37ºC for same period of bleaching treatment. Procedures for bonding composite resin to enamel were carried out according to manufacturer instructions. After storage in distilled water at 37ºC for 24 hours, all samples were submitted to shear bond strength test. G2 had the highest mean value (14.86 MPa) while G5 had the lowest (12.32 MPa). The comparison of groups by 2-way ANOVA showed that there were no significant differences for either of the factors considered in this study (bleaching and photopolymerization source), hence the interaction between these factors. It was therefore possible to conclude that neither enamel bleaching nor the photopolymerization source used had any influence on enamel shear bond strength.